3-Hydroxyhexanoate-based polycationic nanoparticle system for delivering reprogramming factors - Varli, Hanife Sevgi; Alkan, Funda; Kirmizitas, Fatma Ceren; Demirbilek, Murat; Lacin, Nelisa Turkoglu (TAYLOR & FRANCIS LTD, 2020)
Aim: In this study, we aimed to develop a polycationic non-viral carrier for the delivery of the reprogramming factors to the L929 fibroblast cell. Methods: We have prepared (3-hydroxybutyrate-co-3-hydroxyhexanoate) PHBHHx-based nanoparticles with the solvent diffusion method. Cytotoxicity of PXNs was determined via MTT assay. Transfection efficiency was evaluated via screening GFP expression by fluorescence microscopy. The expression of reprogramming factors (Oct4, Klf4, and Sox2) was determined by RT-qPCR. Results: PXNs with 32.9 +/- 0.41 mV zeta potential and 177.6 +/- 0.80 nm size were used for transfection of L929 Fbroblast cells. The percentage of cell viability of PXN were between 91.8%(+/- 2.9) and 42.1%(+/- 1.3). The transfection efficiency was found as 71.6%(+/- 3,5). According to RT-qPCR data, the rate of transfection factors was significantly increased after the 11th cycle compared to non-transfected cells. Based on these results, it can be concluded that newly developed PXN is thought to be an effective tool for reprogramming cells.
Keywords: Reprogramming factors; PXN; nanoparticle; fibroblast; non-viral; PLURIPOTENT STEM-CELLS; GENE; TRANSFECTION; EFFICIENCY; Chemistry; Engineering; Pharmacology & Pharmacy